Die Aura der fünfziger Jahre in Rifbjergs Roman Die chronische Unschuld - Kaszyński, Stefan H (Studia Germanica Posnaniensia, 2018)
The paper offers a new interpretation of a Scandinavian novel which has become one of the most popular Scandinavian novels in the world. New methods of analysis of literary work have been applied to identify the elements of Klaus Rifbjerg's Chronic innocence (1958) which made that fiction a world success. In addition to the clearly outlined elements of the success strategy, e.g. critique of the middle class educational novel model, creative attitude towards the language, and instrumental approach to the poetics of popular literature, it was the elusive and unique climate of the 1950ties carefully coded in Chronic innocence which granted the novel an everlasting value. Rifbjerg's novel, once interpreted as a protest of a generation against fossilized forms of social behavior and moral norms, today fascinates the reader with its unique climate: the protest which transformed into nostalgia.